Audiovisual processing and selective attention in adult dyslexic readers: An event‐related potential study. (22nd December 2020) - Menashe, Shay
Abstract : Developmental dyslexia is a specific reading disability characterized by decoding and spelling deficits that continue into adulthood. Because reading involves both attentional functions and audiovisual (AV) processing, the aim of this study was to explore the associations between the two factors in adult dyslexic readers. Adult non‐impaired and dyslexic readers undertook alphabetic and non‐alphabetic tasks, each composed of three experimental blocks. Two experimental blocks contained left and right spatial selective attention manipulations, and another block included central presentations of the stimuli. Event‐related potential (ERP) and behavioural parameters were collected and analysed, particularly with respect to the N1‐P2 ERP complex. The dyslexic readers showed deviant patterns of amplitudes when it came to alphabetic stimuli processing. However, there was no difference between the two groups with regard to the non‐alphabetic stimuli. These results imply that adult dyslexic readers allocate altered attentional resources when it comes to the processing of AV alphabetic stimuli.